Primary Anterior Abdominal Wall Leiomyoma - a Rare Case with a Common Approach - Muhammad Izzuddin Hamzan; Ariffuddin Ishak; Normala Basiron (Gynecology Obstetrics & Reproductive Medicine)
Extra-peritoneal leiomyoma is a rare condition with the recognised etiologic factor being direct seeding of the site by a prior uterine surgery with a right metabolic environment. We report a rare case of abdominal wall leiomyoma developing in a fertile woman with no known predisposing factor and highlight the common approach to establish the diagnosis so as to deliver appropriate treatment to the patient.